Experiences With and Preferences for Drip Irrigation Systems in Punjab, Pakistan - International Food Policy Research Institute; Duke Kunshan University; New York University; University of Agriculture, Faisalabad (International Food Policy Research Institute, 2018)
The data in this study were collected to assess preferences with respect to drip irrigation systems, which was promoted under Punjab Irrigated-Agriculture Productivity Improvement Project (PIPIP) in Pakistan. The survey was conducted among 475 households across four districts (Attok, Chakwal, Layyah, and Sahiwal) in the Punjab province of Pakistan. These districts capture contrasting agroecological zones as well as contrasting agricultural systems. The survey was designed primarily to capture differential preferences along a gradient of drip irrigation experience and exposure. In addition, the survey collects household information such as education, farm holdings, cropping systems, and patterns.